Rare tumors in pediatrics: First report in Argentina - Casanovas, Alejandra (2021)
Introduction: Collaborative clinical trials have enlarged the knowledge base about pediatric tumors; however, this is not the case for rare tumors (RT).Objective: To describe the prevalence, clinical characteristics, and course of RT in pediatric patients diagnosed at Hospital Garrahan.Material and methods: Descriptive, retrospective study of patients aged 0-18 years diagnosed with a RT and admitted between January 2007 and December 2017.Results: Out of 1657 patients diagnosed with solid tumors, 164 (9.9 %) were RT; 71.95 % (118) of patients were younger than 14 years and 81.7 % (130) were males. In order of frequency, RT were thyroid carcinoma (60), adrenal carcinoma (14), lung tumors (14), melanoma (13), salivary gland cancer (11), gastrointestinal tumors (8), non-germ cell gonadal tumors (7), pancreatic tumors (7), renal carcinomas (6), nasopharyngeal carcinomas (5), pheochromocytoma and paraganglioma (5), and thymic carcinoma in 1 patient. Treatment depended on tumor type and stage. The median follow-up was 34.9 months (range: 1-128.5 months); 133 patients (78.7 %) are alive and only 10 patients (6 %) were lost-to-follow-up.Conclusion: The prevalence of RT was 9.9 %. Twenty-seven percent occurred in adolescents. The most frequent tumors included thyroid carcinoma, adrenal carcinoma, and melanoma. Treatment and course varied based on tumor histology. Predisposing molecular alterations were found in 5.3 % of patients; 3.5 % had a history of cancer.